EFEITOS DOS FLAVONOIDES NARINGINA E NEOHESPERIDINA SOBRE CÉLULAS BRIN-BD11 SECRETORAS DE INSULINA SUBMETIDAS AO ESTRESSE OXIDATIVO INDUZIDO PELO H2O2. - Maestri, Juliana Sousa (2011)
Pancreatic cells show up lower level of free radicals detoxication then, in present study, assessed the possible cytoprotective effect of flavonoids naringin, neohesperidin and quercetin. The oxidative stress induced by H2O2 (6.25-600 M) was standardized in BRIN-BD11 cells. Measurement of the half maximal inhibitory concentration (IC50) of H2O2 in chronic oxidative stress (24 hours) resulted in 180M. However, when H2O2 was incorporated with DMSO, the IC50 was 75M. In acute oxidative stress (2 hours) assay IC50 H2O2 was 350M. Flavonoids (1.25 - 80 μM) did not show cytotoxic effects after 24 hours. In the same away insulinotropic effects were not observed from treatment with the flavonoids (1.25 - 80M) for 24 hours. Cytoprotective effects of flavonoids (2.5, 5, 10M) on BRIN-BD11 cells were not observed in simultaneous exposure to H2O2 (350 M lethal dose) for 2 hours or for 24 hours (37.5M- sub-lethal and 75M- lethal dose). Also the flavonoids not conferred cytoprotection to cells in pre-treatment for 24 hours. However the flavonoids present scavenger activity. In fact, naringin and neohesperidin (10M) in PBS buffer (acute assay), showed significant scavenger activity. The cytoprotective effects of flavonoids only were observed on BRIN-BD11 cells when using in association, it revealed synergic effects.